2020
DOI: 10.3390/nu12103136
|View full text |Cite
|
Sign up to set email alerts
|

Soy-Based Infant Formula is Associated with an Increased Prevalence of Comorbidities in Fragile X Syndrome

Abstract: A large number of adults and children consume soy in various forms, but little information is available regarding potential neurological side effects. Prior work indicates an association between the consumption of soy-based diets and seizure prevalence in mouse models of neurological disease and in children with autism. Herein, we sought to evaluate potential associations between the consumption of soy-based formula during infancy and disease comorbidities in persons with fragile X syndrome (FXS), while contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…A national registry of FXS families maintained by FORWARD was utilized to conduct a retrospective survey study evaluating associations between early childhood feeding practices and the severity of common FXS phenotypes. A detailed description of the study design, questionnaire, study population, recruitment success, and data collection have been previously described [ 19 ]. Briefly, the 55-point questionnaire, Fragile X Syndrome Nutrition Study, assessed demographics, infant feeding practices, frequency and severity of seizures, cognitive ability, autistic behaviors and comorbid diagnoses in an FXS population by parental survey.…”
Section: Methods and Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…A national registry of FXS families maintained by FORWARD was utilized to conduct a retrospective survey study evaluating associations between early childhood feeding practices and the severity of common FXS phenotypes. A detailed description of the study design, questionnaire, study population, recruitment success, and data collection have been previously described [ 19 ]. Briefly, the 55-point questionnaire, Fragile X Syndrome Nutrition Study, assessed demographics, infant feeding practices, frequency and severity of seizures, cognitive ability, autistic behaviors and comorbid diagnoses in an FXS population by parental survey.…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…Phase 2 occurred from 19 December 2019 through 7 February 2020 and consisted of mailing the questionnaire and reminders to participants who agreed to participate in the study. The participation response rate was 89% [ 19 ].…”
Section: Methods and Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Westmark and colleagues contribute a survey-based study to this Special Issue regarding associations between caregiver-reported use of soy-based infant formula and disease comorbidities in their children with fragile X syndrome [ 7 ]. Fragile X is a rare developmental disability characterized by intellectual disability, autism and seizures.…”
mentioning
confidence: 99%